The association between high jugular bulb and mastoid pneumatization in adults - Chen, Chenyu; Weng, Simin; Chen, Zhifeng; Chen, Yuqing; Yao, Guangnan; Huang, Xiying; Gu, Xi; Lin, Chang (Frontiers in Neurology, 2024)
Purpose The purpose of this study was to analyze the relationship between the degree of high jugular bulb (HJB) and mastoid pneumatization using high-resolution computed tomography (HRCT). Methods Between April 2019 and June 2022, HRCT of the temporal bone was retrospectively analyzed in 1,025 patients. By excluding the other coexistent pathologies, 113 patients with HJBs were recruited for the study. The degree of the HJBs were defined as follows: Grade I, JB situated between inferior annulus of tympanic membrane and cochlear basal turn (CBT). Grade II, JB situated between CBT and lateral semicircular canal (LSC). Grade III, JB situated above LSC. The volume of mastoid pneumatization was based on HRCT images using a 3D reconstruction. Results There were 32 male and 81 female subjects (mean age, 41.2 ± 14.0 years; age range, 18–80 years). The male group included 16 Grade I, 28 Grade II and 6 Group III HJB subjects. The female group included 38 Grade I, 62 Grade II and 31 Group III HJB cases. In the different groups of HJB, the mastoid cell volume differences were also not statistically significant (p = 0.165). In the classification, Grade II was most common (90/181, 49.7%). Conclusion This study found no correlation between mastoid air cell volume and HJB, suggesting that HJB may not affect the mastoid air cell development and disease occurrence. These data must be considered exploratory, requiring more extensive cross-sectional studies.